The pursuit of certainty: religious and cultural formulations - James, Wendy (Uses of knowledge, 1995)
"The peoples of the world are now facing economic integration and social interaction on a wider scale than ever before. But has this produced a greater sense of common reason, or shared world citizenship? Contemporary global communication, itself celebrating diversity, has paradoxically stimulated local commitments to exclusive ethnic, cultural and religious identity. The chapters in this book explore the ways in which anthropology can throw light on these diverging new 'certainties', often possessive of place, bodily substance or cultural heritage and often claiming divine justification." "The Pursuit of Certainty is a convincing demonstration of anthropology's relevance to the contemporary world and its turbulence. It offers ground-level insights into a growing global consensus about the primacy of cultural difference; into the shrill new certainties which are spreading in some areas though being resisted in others: and into the 'post-Enlightenment' rise of religious justification in human affairs."--Jacket